2022
DOI: 10.1097/rli.0000000000000932
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Automatic Bone Marrow Apparent Diffusion Coefficient Measurements From Whole-Body Magnetic Resonance Imaging in Patients With Multiple Myeloma

Abstract: ObjectivesDiffusion-weighted magnetic resonance imaging (MRI) is increasingly important in patients with multiple myeloma (MM). The objective of this study was to train and test an algorithm for automatic pelvic bone marrow analysis from whole-body apparent diffusion coefficient (ADC) maps in patients with MM, which automatically segments pelvic bones and subsequently extracts objective, representative ADC measurements from each bone.Materials and MethodsIn this retrospective multicentric study, 180 MRIs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…A connection between stages of diffuse infiltration severity in MRI and PCI, 39,44–47 as well as between signal intensities/ADC-values and PCI, 43,48,49 has been described. However, to the best of our knowledge, these have not yet been used to predict PCI from MRI.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A connection between stages of diffuse infiltration severity in MRI and PCI, 39,44–47 as well as between signal intensities/ADC-values and PCI, 43,48,49 has been described. However, to the best of our knowledge, these have not yet been used to predict PCI from MRI.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier approaches on automatic BM segmentation [40][41][42] reported results that were markedly worse than the benchmark for manual segmentation set by interrater experiments. Recently, first BM segmentation algorithms were presented which allowed BM segmentation from T1w images 25 and ADC-maps 43 with a quality similar to manual segmentations by a radiologist, and performed relatively robust even in external multicentric test sets. In the current study, we trained a nnU-Net on 470 cases with a wide variety of pathologies and several different MRI protocols and scanners represented in the training data sets, to perform individual segmentation of the right and left hip bone from T1-w images.…”
Section: Automated Bone Marrow Segmentationmentioning
confidence: 99%
“…In addition, many DL models are dedicated to segmenting bones and vertebrae from radiological images ( Huang et al, 2020 ; Wennmann et al, 2022a ). Klinder et al ( Klinder et al, 2009 ) reported an automated model-based vertebral detection, identification, and segmentation method; this model can achieve an identification success of more than 70% for a single vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to implement radiomics in clinical practice for MM patients, methods that allow the segmentation of multiple focal lesions and extended areas of diffuse infiltration or whole bones are required since the manual segmentation of this scale is extremely tedious and potentially unreliable. Methods such as the atlas-based semi-automatic segmentation of whole-body diffusion-weighted imaging and deep learning applications combined with radiomics have already been proposed [ 31 , 42 , 43 , 44 ] and may be the solution to the future translation of radiomics research to the clinic.…”
Section: Discussionmentioning
confidence: 99%